2012
DOI: 10.1039/c2cc33439a
|View full text |Cite
|
Sign up to set email alerts
|

Porous carbon materials with a controllable surface area synthesized from metal–organic frameworks

Abstract: Carbonization of zinc containing metal-organic frameworks produces porous carbon materials with an interesting linear relationship between the Zn/C ratio of the precursors and the surface area of the resulting carbon materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
128
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 67 publications
3
128
0
1
Order By: Relevance
“…[52] MOFs, owing to their high surface area, inherent porosity and ordered structure, have been widely used as precursors to derive nanoporous carbonaceous structures. [47,53] The use of Zn-based MOFs/ZIFs has been identified as an easy and direct way of fabricating NPC. The conversion of organic ligands into carbon reduces Zn moieties which are eventually evaporated from the product at elevated temperature (≈900 °C).…”
Section: Orr Catalysismentioning
confidence: 99%
“…[52] MOFs, owing to their high surface area, inherent porosity and ordered structure, have been widely used as precursors to derive nanoporous carbonaceous structures. [47,53] The use of Zn-based MOFs/ZIFs has been identified as an easy and direct way of fabricating NPC. The conversion of organic ligands into carbon reduces Zn moieties which are eventually evaporated from the product at elevated temperature (≈900 °C).…”
Section: Orr Catalysismentioning
confidence: 99%
“…[38,41,42] 1c and 3D mesoporous carbon have a wide distribution through micro-and mesopore region. [43,44] The meso-C mentioned above mainly possesses mesopores, which correlates with its surface area data. Across the reaction conditions of direct carbonized MOFs, it might be suggested that in MOF-5 derived system, longer calcination time and higher calcination temperature benefit the generation of larger surface areas, but the temperature higher than 1000 ℃ may weaken that positive action.…”
Section: Introductionmentioning
confidence: 97%
“…The surface areas of the direct calcined MOF-5 are relatively low but the data reported by others (Table 1, Nos. 5-11) [37][38][39][40][41][42][43] generally showed better values: besides meso-C (Table 1, No. 7), [39] all these materials have the BET surface area larger than 1400 m 2 /g, which is much higher than surface areas of APC series calcined at corresponding temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Other than silica and metal oxides, catalytic supports of carbon-based materials including activated carbon, mesoporous carbon, and graphite have also been widely used owing to their high stability towards acidic or basic environments. [8] Moreover, another advantage of carbon-based supports is the possible interactions between the catalytically active species and the carbon surface. [9] Despite these pioneering studies, the development of new nanoporous materials is still highly demanded for various applications.…”
mentioning
confidence: 99%